Sensitivity analysis and optimum design of reinforced concrete frames according to Eurocode 2. Issue 12 (1st December 2020) - Martins, Alberto M. B.; Simões, Luís M. C.; Negrão, João H. J. O.; Lopes, Adelino V.
Abstract : This article presents an optimization-based computational method to assist in the design of reinforced concrete framed structures. The design of these structures is posed as a multi-objective optimization problem seeking cost minimization, strength and serviceability design objectives defined according to Eurocode 2 provisions. An entropy-based approach is used to obtain the solution of the minimax problem by minimizing a convex scalar function. Special emphasis is placed on the sensitivity analysis, which is crucial for the performance of the optimization algorithm. The discrete direct method was used to compute the sensitivities of the design objectives, the allowable values of which are dependent on the design variables. The cross-sectional dimensions of beams and columns and the longitudinal and shear reinforcement areas are the design variables. Verification examples and the optimization of a real-sized building structure are presented to illustrate the features of the developed method.